Neurobrucellosis: a retrospective cohort of 106 patients - Fatemeh Arazi; Mahboubeh Haddad; Fereshte Sheybani; Mohammad Taghi Farzadfard; Majid Khadem Rezaeian (Tropical Medicine and Health)
Abstract Background Neurobrucellosis, a serious central nervous system infection caused by Brucella species, presents significant challenges due to its diverse clinical manifestations and the risk of long-term complications and poor outcomes. Identifying predictors of adverse outcomes is critical for improving patient management and overall prognosis. Objectives This study aimed to evaluate the long-term morbidity and mortality associated with neurobrucellosis and to identify key predictors of adverse outcomes. Methods We performed a retrospective cohort study of 106 neurobrucellosis patients treated at two major referral centers in Mashhad, Iran, from March 21, 2011, to March 20, 2022. We analyzed clinical, neuroimaging, and laboratory data, and estimated survival probabilities using Kaplan–Meier analysis. Long-term morbidity was evaluated using the Glasgow Outcome Scale. Results The median age of the cohort was 30 years (IQR: 21.8–46.3). The median length of hospital stay was 11 days (IQR: 7–19.8), with an in-hospital mortality rate of 4.7% (n = 5). Survival probabilities were 92.2% (SE = 0.027) at 1 month and 90.1% (SE = 0.030) at 6 months. The median follow-up duration was 52 months (IQR: 35–77). At follow-up, 23.5% (n = 20) of patients had an unfavorable outcome based on the Glasgow Outcome Scale. Predictors of mortality included older age, altered level of consciousness, seizures, elevated body temperature on admission, and white matter changes on neuroimaging. Conclusion Neurobrucellosis is associated with significant long-term morbidity and mortality. Key predictors of mortality include older age, altered level of consciousness, seizures, elevated body temperature on admission, and white matter changes. Identifying these predictors can help in targeting therapeutic strategies and improving patient outcomes through early intervention and close monitoring.